BANKRUPTCY ANALYSIS USING THE ALTMAN Z-SCORE MODEL IN AIRLINE COMPANIES - Siti Alfina Nurhidayati; Siti Ridloah (COMPETITIVE, 2026)
Bankruptcy prediction is on essential for evaluating the financial stability of companies, particularly in the aviation industry, which is highly vulnerable to economic fluctuations, high operational costs, and external shocks. The purpose of this study is to evaluate the bankruptcy potential of airlines listed on the Indonesia Stock Exchange using the Altman Z-Score and classify companies into safe, grey, or distress zones. A quantitative descriptive method was employed, utilizing secondary financial data from 2021 to 2024, focusing three companies: PT Air Asia Indonesia Tbk consistently recorded an extremely low Z-Score ranging from -17.52 to -20.24, placing the company in the distress zone throughout the entire period. PT Garuda Indonesia (Persero) Tbk reveals fluctuating performance, with severe distress in 2021 (–12.02), a temporary recovery in 2022 (2.00), but the next period saw a decline into the distress zone in 2023 (–1.42) and 2024 (–1.89). Meanwhile, PT Jaya Trishindo Tbk had a Z-score of 2.82 in 2021, above the safe threshold of 2.60, indicating the safe zone. However, from 2022 to 2024, the company's Z-score declined sharply, falling below 1.10, ranging from –2.96 to 0.98, entering the distress zone, with the lowest in 2022. The Altman Z-Score method indicates that the observed companies experienced significant financial distress during the study period, with Z-Scores below 1.10 from 2021 to 2024, highlighting that external shocks during the COVID-19 pandemic significantly weakened revenue performance while simultaneously accelerating the accumulation of corporate debt, thereby increasing bankruptcy risk in the aviation sector.